2011
DOI: 10.3141/2237-16
|View full text |Cite
|
Sign up to set email alerts
|

Accident Prediction Models for Winter Road Safety

Abstract: Most accident prediction models are developed with single-level count data models, such as the traditional negative binomial models with fixed or varying dispersion parameters, assuming independence of data. For many accident data sets in road safety analysis, especially those that are highly disaggregated (hourly data), a hierarchical structure in the data often manifests in some form of correlation. Crash prediction models developed with aggregate data could produce biased results because of the assumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 44 publications
2
3
1
Order By: Relevance
“…A prominent extension of the NB model is the HTNB model, which is a more flexible approach to address unobserved heterogeneity through allowing dispersion parameter to vary across crash sites as a function of site-specific characteristics. The superiority of HTNB model over the traditional NB model has been confirmed in previous studies ( 12 , 13 , 24 , 25 ). Similar to the traditional NB model, the HTNB model uses the same probability density function as that given in Equation 2.…”
Section: Methodssupporting
confidence: 72%
“…A prominent extension of the NB model is the HTNB model, which is a more flexible approach to address unobserved heterogeneity through allowing dispersion parameter to vary across crash sites as a function of site-specific characteristics. The superiority of HTNB model over the traditional NB model has been confirmed in previous studies ( 12 , 13 , 24 , 25 ). Similar to the traditional NB model, the HTNB model uses the same probability density function as that given in Equation 2.…”
Section: Methodssupporting
confidence: 72%
“…Note that these results are similar with that of a past study Hermans et al (2006a) using data from 37 sites. However, our results are different from the study conducted by Usman (2011) that found a negative relationship between visibility and crash frequency during a storm event. Note that the models developed in this research are not winter-storm event based models but rather consider all the weather-related crashes that occurred during the winter seasons.…”
Section: Visibility (In Mile)contrasting
confidence: 99%
“…The results make intuitive sense as higher wind speeds could cause blowing snow effects, which might impair driver performance during winter seasons. This result is in agreement with previous research findings ( Usman, 2011).…”
Section: Wind Speedsupporting
confidence: 94%
See 1 more Smart Citation
“…The occurrence time and location of this natural phenomenon are extremely difficult to predict because rapid transitions between dry, wet, snow, and ice are common on such surfaces. This recurrent condition caused by water, ice, and snow causes many accidents worldwide [ 1 , 2 , 3 , 4 , 5 ]. Given the terrain in Korea, many roadways pass through mountainous areas [ 6 ].…”
Section: Introductionmentioning
confidence: 99%